GEOCHEMISTRY AND PETROGENESIS OF SILLS IN LAVASANAT REGION, TEHRAN, IRAN - Bina, Mehdi; Arian, Mohammad Ali; Pourkermani, Mohsen; Bazoobandi, Mohammad Hasan (Geosaberes; Vol 11 (2020): Vol 11 (2020), 2020)
The study area is located in Lavasanat region in the east of Tehran Province in the Central Alborz zone. The outcrops in this region are mainly associated with Karaj formation and belong to the upper Eocene to Oligocene periods. These outcrops consist of two intrusions: one in the north and the other in the northeast of Lavasanat. These outcrops are scattered over an area of approximately 337km 2 . In the study region, there are various intrusive igneous rocks, while numerous intrusive igneous rocks are scattered in the form of sills and dikes. These rocks include a range of rocks from diorite gabbro to diorite, monzonite, and syenite. The weathered colors of these rocks are black, brown and gray. The outcrops of these sills are mainly present in the middle-northern part of the quadrangle geological map of the east of Tehran. In different diagrams of the magma series, the study rocks are classified as alkaline, calc-alkaline, and shoshonite, which may indicate magma contamination. An analysis of the variations of the classical elements and trace elements, the spider plots, and interpretations of these plots confirms the relationship of these rocks with the subduction zone and continental arc. To find the tectonic position of the sills in the study area based on the geochemical diagrams, we selected samples from the within-plate (WIP) and arc zones.